Utilização do complexo de rutênio cis- [Ru(bpy)2(NO2)(NO)](PF6)2) para reverter e/ou prevenir a disfunção endotelial na hipertensão arterial - Vatanabe, Izabela Pereira (2016)
The endothelium is a monolayer of cells that extends on the vascular inner surface, responsible for the modulation of vascular tone. By means of the release of nitric oxide (NO), the endothelium has an important protective function against cardiovascular diseases, producing vasodilation by several mechanisms and generating a series of other effects, since at high concentrations it may produce toxic effects to the cells. However, endothelial dysfunction is characterized mainly by the decreased ability of endothelial cells to release NO, which may be due to reaction with superoxide anion (O2 -) and formation of peroxynitrite (ONOO-). In previous studies, it was found that ruthenium complexes can also inactivate O2 - and NO release. However, through vascular reactivity technique in aortic hypertensive and normotensive rats, and detection study of released NO in endothelial cells, the objective of this study was to evaluate the potential of the drug cis- [Ru(bpy)2(NO2)(NO)](PF6)2 as a pharmacologic strategy to reverse and/or prevent endothelial dysfunction found in the arterial hypertension model 2K-1C as well as to perform the pharmacological characterization of the dependent effects removal of O2 - and NO release induced by these drugs. Thus our major vascular reactivity results indicated that the BPY concentration of 0.1 μM was able to reverse the endothelial dysfunction present in the aortas of animals 2K-1C. Likewise, its positive control, Deta-NO in a specific concentration of 10 μM was able to reverse endothelial dysfunction, besides presenting a potentiating effect in the presence of endothelium. Furthermore, our results indicate that the lowest detection of NO in HUVECs treated with Ang. II, in addition to BPY compound occurs by the increased formation of O2 -, since in the presence of SOD there was an increased release of NO by BPY. Furthermore, it was observed that the BPY releases NO in solution in a sustained concentration-dependent form, where the presence of the endothelial cells increased and Angiotensin II reduces NO release, indicating a reduction or oxidation in BPY compound and also degradation of NO the formation of O2 -.